KEEFEKTIFAN PEMBINAAN PROFESIONALISME GURU IPA MELALUI TEACHING CLINIC MGMP - Nyoman Murniati, Ngurah Ayu (Jurnal Penelitian Pembelajaran Fisika, 2012)
ABSTRAK Â Facts on the ground indicate that many science teachers have educational qualifications from undergraduate ph ysics education, biology, and chemistry education. They will not teach well junior biology material, and vice versa. It is a challenge science teachers professional development. Teaching Clinic is a teaching clinic set up to solve the problems of the teaching profession. Through Teaching Clinic teachers are expected to improve the profession independently and sustainably. Formulation of the research problem is how the effectiveness of professional development of teachers through the Teaching Clinic? Design research is education quantitative research The results showed an increase in performance science teacher before and after participating in Teaching Clinic. This means that science teachers professional development through effective Teaching Clinic. The conclusions of this study are Teaching Clinic research is can be used as a science teacher professional development. Through the Teaching Clinic to improve service quality in building and developing the junior high science teacher professionalism. Keywords: development, professionalism, Teaching, Clinic